Influence of internal and external factors on school performance in primary education from a global perspective - Del Castillo Guardamino, Carlos Antonio (2015)
Objective: This research examines  the relationship of various factors on  student achievement, as measured  by the PISA test, which is applied in  more than 60 countries every three  years. The aim is to analyze which of  them have more to results.  Method: lts main focus is the  evaluation of the ability of reading  and mathematical understanding at  various levels. There are many  variables that can influence those  outcomes, generically classified as  internal (inherent in the education  system) and external (environmental  or ambient).  Results: The data used come from  the World Bank for the past 10 years  (most recent data 2012). The results  indicate that although each of the  selected variables exerts some  influence on the quality of education  as measured by the academic  performance are external variables  that have greater explanatory power  of the results, which corroborates the  findings of many previous studies  made at the level of countries and  regions. Conclusion: This investigation has  simplified global model that sought  to prove that the premises that were  built decades ago on the importance  of factors not directly linked to the  education system, still in effect, and  which are those elements of the  environment, the macroeconomic  and welfare conditions, which exert a  greater influence on the results of  achievement tests